Information accessibility and knowledge creation: The impact of Google's withdrawal from China on scientific research - Katrin Hussinger; Lorenzo Palladini (ZEW - Leibniz-Zentrum für Europäische Wirtschaftsforschung, 2024)
How important is Google for scientific research? This paper exploits the exogenous shock represented by Google's sudden withdrawal of its services from mainland China to assess the importance of access to information for the knowledge production function of scientific scholars in the field of economics. For economists, a type of scholar with a simple knowledge production function, results from difference-in-difference analyses, which compare their scientific output to scholars located in the neighboring regions, show that the scientific productivity declines by about 28% in volume and 30% in terms of citations. These results are consistent with the view that information accessibility is an important driver of scientific progress. Considering that the negative effect of the shock is stronger for top scholars located in China, Google's sudden exit bears the risk that researchers lose touch with the research frontier and persistently lag behind their foreign peers.
Keywords: D83; L86; 330; information accessibility; academic publications; knowledge production; Google; China